A Review of Observational Pain Scales in Nonverbal Elderly With Cognitive Impairments - Juyoung Park; Castellanos-Brown, Karen; Belcher, John (Research on Social Work Practice, 2010)
Objective: Pain assessment for nonverbal older adults with cognitive impairments or dementia presents many challenges, and it is important to determine which scales are most useful in assessing pain among this population. Method: In this review 11 observational scales for assessment of pain in older adults with dementia or cognitive impairments are evaluated in four areas: pain indicators, reliability, validity, and clinical utility of the measure. Results: Results indicate that various scales are available for assessing pain in cognitively impaired or demented older adults who are unable to report their pain, but future research should focus on further psychometric evaluations. Conclusions: Implications include that social workers should be trained as raters of pain assessment methods.